Ultrasound visual feedback for acquired apraxia of speech: A case report - Preston, Jonathan L; Leaman, Marion (Aphasiology, 2014)
Background: Individuals with acquired apraxia of speech (AOS) can lose precision of articulatory movements, including the ability to achieve correct production of specific sounds or sound sequences. Novel treatment approaches should be explored to enhance treatment outcomes.Aims: To evaluate the clinical feasibility of ultrasound visual feedback of the tongue for addressing errors on rhotics in a patient with AOS. Ultrasound visual feedback was used to provide knowledge of performance to the participant.Methods & Procedures: A multiple baseline single case report is presented to evaluate a treatment programme that uses visual feedback of the participant's tongue from real-time ultrasound images. A blocked practice schedule was implemented during 12 one-hour therapy sessions; 30 minutes involved ultrasound visual feedback (10 minutes of pre-practice and 20 minutes of practice) and 20 minutes involved non-ultrasound practice. Cues were provided to modify tongue shape to achieve perceptually accurate production of rhotics, along with practice trials with increasing levels of phonetic complexity. The feedback type (verbal knowledge of performance and knowledge of results) and feedback frequency (number of trials with feedback) were structured to adhere to principles of motor learning.Outcomes & Results: The participant demonstrated moderate evidence of acquisition of prevocalic rhotics and strong evidence of acquisition of postvocalic rhotics during treatment. There was evidence of retention and generalisation only for postvocalic rhotics. An untreated context was probed regularly and showed no evidence of improvement.Conclusion: The results provide preliminary support for the feasibility of this treatment approach for improving speech accuracy in adults with acquired AOS. The improvements in stimulability for the treated sound sequences could be used to foster further motor learning. © 2014 © Taylor & Francis Group.
26 citations (Crossref) [2023-10-31] Citation Key Alias: lens.org/120-649-995-107-292 tex.type: [object Object]
Keywords: Apraxia; Articulation; Clinical feasibility; Feedback; Feedback frequency; Feedback type; Generalisation; Motor learning; Patient treatment; Speech; Ultrasonics; Ultrasound; Ultrasound images; Visual communication; Visual feedback; adult; aphasia; apraxia of speech; article; association; ataxic aphasia; case report; cerebrovascular accident; dept.cmd; error; female; human; knowledge; learning; middle aged; peer-reviewed; phonetics; speech and language assessment; speech language pathologist; tongue; ultrasound; visual analysis; visual feedback; vocalization

Identifying residual speech sound disorders in bilingual children: A japanese-english case study - Preston, Jonathan L.; Seki, Ayumi (American Journal of Speech-language Pathology, 2011)
Purpose: To describe (a) the assessment of residual speech sound disorders (SSDs) in bilinguals by distinguishing speech patterns associated with second language acquisition from patterns associated with misarticulations and (b) how assessment of domains such as speech motor control and phonological awareness can provide a more complete understanding of SSDs in bilinguals. Method: A review of Japanese phonology is provided to offer a context for understanding the transfer of Japanese to English productions. A case study of an 11-year-old is presented, demonstrating parallel speech assessments in English and Japanese. Speech motor and phonological awareness tasks were conducted in both languages. Results: Several patterns were observed in the participant's English that could be plausibly explained by the influence of Japanese phonology. However, errors indicating a residual SSD were observed in both Japanese and English. A speech motor assessment suggested possible speech motor control problems, and phonological awareness was judged to be within the typical range of performance in both languages. Conclusion: Understanding the phonological characteristics of the native language can help clinicians recognize speech patterns in the second language associated with transfer. Once these differences are understood, patterns associated with a residual SSD can be identified. Supplementing a relational speech analysis with measures of speech motor control and phonological awareness can provide a more comprehensive understanding of a client's strengths and needs.
13 citations (Crossref) [2023-10-31] Citation Key Alias: lens.org/109-148-393-297-363 tex.eissn: [object Object] tex.orcid-numbers: [object Object] tex.researcherid-numbers: [object Object] tex.unique-id: [object Object]
Keywords: Articulation; Assessment; Bilingualism; Residual speech sound disorders; Speech motor control; dept.cmd

Phonetic variability in residual speech sound disorders exploration of subtypes - Preston, Jonathan L.; Koenig, Laura L. (Topics in Language Disorders, 2011)
Purpose: To explore whether subgroups of children with residual speech sound disorders (R-SSDs) can be identified through multiple measures of token-to-token phonetic variability (changes in one spoken production to the next). Method: Children with R-SSDs were recorded during a rapid multisyllabic picture naming task and an oral diadochokinetic task. Transcription-based and acoustic measures of token-to-token variability were derived. Articulation accuracy and general indices of language skills were measured as well. Results: Low correlations were observed between transcription-based and acoustic measures of phonetic variability, and among the acoustic measures themselves. Children who were the most variable on one measure were not necessarily highly variable on other measures. Transcription-based measures of variability were associated with language skills. Conclusions: Measures of phonetic variability did not identify children in the sample as consistently high or low. Data do not support the notion that clear subgroups based on phonetic variability can be reliably identified in children with R-SSDs. The link between highly variable phonetic output (quantified by transcription-based measures) and lower language skills requires further exploration.
18 citations (Crossref) [2023-10-31] tex.orcid-numbers: Preston, Jonathan/0000-0001-9971-6321 tex.researcherid-numbers: Preston, Jonathan/E-9310-2010 tex.unique-id: ISI:000290432200007
Keywords: acoustic analysis; dept.cmd; phonetic variability; residual speech sound disorders

Ultrasound biofeedback treatment for persisting childhood apraxia of speech - Preston, Jonathan L.; Brick, Nickole; Landi, Nicole (American Journal of Speech-language Pathology, 2013)
Purpose: The purpose of this study was to evaluate the efficacy of a treatment program that includes ultrasound biofeedback for children with persisting speech sound errors associated with childhood apraxia of speech (CAS). Method: Six children ages 9-15 years participated in a multiple baseline experiment for 18 treatment sessions during which treatment focused on producing sequences involving lingual sounds. Children were cued to modify their tongue movements using visual feedback from real-time ultrasound images. Probe data were collected before, during, and after treatment to assess word-level accuracy for treated and untreated sound sequences. As participants reached preestablished performance criteria, new sequences were introduced into treatment. Results: All participants met the performance criterion (80% accuracy for 2 consecutive sessions) on at least 2 treated sound sequences. Across the 6 participants, performance criterion was met for 23 of 31 treated sequences in an average of 5 sessions. Some participants showed no improvement in untreated sequences, whereas others showed generalization to untreated sequences that were phonetically similar to the treated sequences. Most gains were maintained 2 months after the end of treatment. The percentage of phonemes correct increased significantly from pretreatment to the 2-month follow-up. Conclusion: A treatment program including ultrasound biofeedback is a viable option for improving speech sound accuracy in children with persisting speech sound errors associated with CAS.
82 citations (Crossref) [2023-10-31] Citation Key Alias: lens.org/001-315-816-076-394 tex.eissn: [object Object] tex.orcid-numbers: [object Object] tex.researcherid-numbers: [object Object] tex.unique-id: [object Object]
Keywords: Adolescent; Apraxias; Articulation; Biofeedback; Psychology; Child; Childhood apraxia of speech; Children; Cues; Efficacy; Feedback; Sensory; Follow-Up Studies; Humans; Intervention; Male; Phonetics; Speech; Speech Disorders; Speech Therapy; Speech sound disorders; Tongue; Treatment Outcome; Ultrasonic Therapy; adolescent; apraxia; article; articulation; association; child; childhood apraxia of speech; children; clinical trial; dept.cmd; echography; efficacy; follow up; human; intervention; male; methodology; pathophysiology; phonetics; physiology; psychophysiology; sensory feedback; speech; speech disorder; speech sound disorders; speech therapy; tongue; treatment outcome; ultrasound therapy

Preschool speech error patterns predict articulation and phonological awareness outcomes in children with histories of speech sound disorders. - Preston, Jonathan L; Hull, Margaret; Edwards, Mary Louise (American journal of speech-language pathology, 2013)
Purpose: To determine if speech error patterns in preschoolers with speech sound disorders (SSDs) predict articulation and phonological awareness (PA) outcomes almost 4 years later. Method: Twenty-five children with histories of preschool SSDs (and normal receptive language) were tested at an average age of 4;6 (years;months) and were followed up at age 8;3. The frequency of occurrence of preschool distortion errors, typical substitution and syllable structure errors, and atypical substitution and syllable structure errors was used to predict later speech sound production, PA, and literacy outcomes. Results: Group averages revealed below-average schoolage articulation scores and low-average PA but ageappropriate reading and spelling. Preschool speech error patterns were related to school-age outcomes. Children for whom >10% of their speech sound errors were atypical had lower PA and literacy scores at school age than children who produced <10% atypical errors. Preschoolers who produced more distortion errors were likely to have lower school-age articulation scores than preschoolers who produced fewer distortion errors. Conclusion: Different preschool speech error patterns predict different school-age clinical outcomes. Many atypical speech sound errors in preschoolers may be indicative of weak phonological representations, leading to long-term PA weaknesses. Preschoolers' distortions may be resistant to change over time, leading to persisting speech sound production problems. © American Speech-Language-Hearing Association.
74 citations (Crossref) [2023-10-31] Place: United States Preston, Jonathan L. Southern Connecticut State University, New Haven, CT, USA. preston@haskins.yale.edu
Keywords: *Articulation Disorders/di [Diagnosis]; *Language Tests; *Phonetics; *Speech; *Speech Articulation Tests; Awareness; Child; Child Language; Child; Preschool; Female; Follow-Up Studies; Humans; Language Disorders/di [Diagnosis]; Literacy; Male; Outcomes; Phonological awareness; Predictive Value of Tests; Psycholinguistics; Reading; Speech Production Measurement; Speech Sound Disorder; Speech production; Speech sound disorders; dept.cmd

Perception of speech sounds in school-aged children with speech sound disorders - Preston, Jonathan L.; Irwin, Julia R.; Turcios, Jacqueline (Seminars in Speech and Language, 2015)
Children with speech sound disorders may perceive speech differently than children with typical speech development. The nature of these speech differences is reviewed with an emphasis on assessing phoneme-specific perception for speech sounds that are produced in error. Category goodness judgment, or the ability to judge accurate and inaccurate tokens of speech sounds, plays an important role in phonological development. The software Speech Assessment and Interactive Learning System, which has been effectively used to assess preschoolers' ability to perform goodness judgments, is explored for school-aged children with residual speech errors (RSEs). However, data suggest that this particular, task may not be sensitive to perceptual differences in school-aged children. The need for the development of clinical tools for assessment of speech perception in school-aged children with RSE is highlighted, and clinical suggestions are provided.
16 citations (Crossref) [2023-10-31] Citation Key Alias: lens.org/110-366-030-100-745 tex.eissn: [object Object] tex.orcid-numbers: [object Object] tex.researcherid-numbers: [object Object] tex.unique-id: [object Object]
Keywords: Child; Female; Humans; Male; Phonetics; Speech; Speech Perception; Speech Sound Disorder; Speech sound disorder; assessment; child; dept.cmd; dept.psy; female; human; male; pathophysiology; phonetics; speech; speech perception; speech sound disorder

Identification of Conductive Hearing Loss in Young Infants Using Tympanometry and Wideband Reflectance. - Prieve, Beth; Vander Werff, Kathy; Preston, Jonathan; Georgantas, Lea (Ear and Hearing, 2013)
Objective: The goal of the study was to evaluate the effectiveness of tympanometry and wideband reflectance (WBR) in detecting conductive hearing loss (CHL) in young infants., Methods: Type of hearing loss was determined using auditory brainstem response using air- and bone-conducted tone bursts in 84 ears from 70 infants (median age = 10 weeks). Of these 84 ears, 60 are included in the current analysis: 43 with normal hearing (NH) and 17 with CHL. Tympanometry was measured using probe tone frequencies of 226, 678, and 1000 Hz. Tympanograms were evaluated in two ways: (1) Acoustic middle ear admittance (Ya, in millimhos); and (2) two-category classification (normal/abnormal), as described by Baldwin (2006). Measures of Ya were evaluated in two ways: by admittance-magnitude tympanograms and calculated admittance magnitude from subcomponents (conductance and susceptance). WBR was measured in response to a chirp stimulus after probe calibration. WBR was analyzed into thirteen 1/3 octave bands. Tests for statistical differences for two-category classification were analyzed using Chi-squared and Ya, and WBR were analyzed using repeated-measures analyses of variances. Cohen's d and likelihood ratios were computed for comparison with statistically significant differences., Results: Ya measured with 678- and 1000 Hz probe tones was significantly different between ears with CHL and NH. Two-category classification of tympanograms using a 1000 Hz probe tone was significantly different between ears with CHL and NH. Neither two-category classification nor Ya was significantly different between ears identified with CHL and NH using a 226 Hz probe tone. WBR was significantly higher in the frequency bands 800 to 2500 Hz and in the frequency band centered at 6300 Hz in infants with CHL. Effect sizes (Cohen's d) were greater than 2 for several WBR frequency bands and Ya measured with 1000 Hz probe tones. The results were similar for calculations of Ya from admittance-magnitude and subcomponent tympanograms. Positive likelihood ratios for WBR ranged between 8.1 and 38, and those for Ya using 1000 Hz ranged between 12.5 and 32., Conclusions: CHL in young infants can be detected well with WBR or tympanometry using probe frequencies of 678 and 1000 Hz., (C) 2013 by Lippincott Williams & Wilkins
30 citations (Crossref) [2023-10-31] Place: (C) 2013 by Lippincott Williams & Wilkins
Keywords: Acoustic Impedance Tests; Acoustic Stimulation; Evoked Potentials; Auditory; Brain Stem; Female; Hearing Loss; Conductive; Hearing Tests; Humans; Infant; Infant; Newborn; Likelihood Functions; Male; Sensitivity and Specificity; acoustic impedance; article; auditory stimulation; conduction deafness; dept.cmd; evoked brain stem auditory response; female; hearing test; human; infant; male; methodology; newborn; sensitivity and specificity; statistical model

Toward improved spectral measures of /s/: results from adolescents - Koenig, Laura L.; Shadle, Christine H.; Preston, Jonathan L.; Mooshammer, Christine R. (Journal of Speech Language and Hearing Research, 2013)
Purpose: This article introduces theoretically driven acoustic measures of /s/ that reflect aerodynamic and articulatory conditions. The measures were evaluated by assessing whether they revealed expected changes over time and labiality effects, along with possible gender differences suggested by past work. Method: Productions of /s/ were extracted from various speaking tasks from typically speaking adolescents (6 boys, 6 girls). Measures were made of relative spectral energies in low-(550-3000 Hz), mid-(3000-7000 Hz), and high-frequency regions (7000-11025 Hz); the mid-frequency amplitude peak; and temporal changes in these parameters. Spectral moments were also obtained to permit comparison with existing work. Results: Spectral balance measures in low-mid and mid-high frequency bands varied over the time course of /s/, capturing the development of sibilance at mid-fricative along with showing some effects of gender and labiality. The mid-frequency spectral peak was significantly higher in nonlabial contexts, and in girls. Temporal variation in the mid-frequency peak differentiated +/- labial contexts while normalizing over gender. Conclusions: The measures showed expected patterns, supporting their validity. Comparison of these data with studies of adults suggests some developmental patterns that call for further study. The measures may also serve to differentiate some cases of typical and misarticulated /s/.
42 citations (Crossref) [2023-10-31] tex.eissn: 1558-9102 tex.orcid-numbers: Preston, Jonathan/0000-0001-9971-6321 tex.researcherid-numbers: Preston, Jonathan/E-9310-2010 tex.unique-id: ISI:000328266600011
Keywords: Acoustics; Adolescent; Adolescents; Development; Female; Humans; Lip; Male; Phonetics; Reference Values; Sex Characteristics; Speech; Speech Acoustics; Speech production; Verbal Behavior; acoustics; adolescent; adolescents; article; comparative study; dept.cmd; development; female; human; lip; male; phonetics; reference value; sexual development; speech; speech production; verbal behavior

Development of an audiovisual speech perception app for children with autism spectrum disorders - Irwin, Julia; Preston, Jonathan; Brancazio, Lawrence; D'Angelo, Michael; Turcios, Jacqueline (Clinical Linguistics & Phonetics, 2015)
Perception of spoken language requires attention to acoustic as well as visible phonetic information. This article reviews the known differences in audiovisual speech perception in children with autism spectrum disorders (ASD) and specifies the need for interventions that address this construct. Elements of an audiovisual training program are described. This researcher-developed program delivered via an iPad app presents natural speech in the context of increasing noise, but supported with a speaking face. Children are cued to attend to visible articulatory information to assist in perception of the spoken words. Data from four children with ASD ages 8-10 are presented showing that the children improved their performance on an untrained auditory speech-in-noise task.
16 citations (Crossref) [2023-10-31] Citation Key Alias: lens.org/022-073-168-350-692 tex.eissn: [object Object] tex.orcid-numbers: [object Object] tex.researcherid-numbers: [object Object] tex.unique-id: [object Object]
Keywords: Attention; Audiovisual Aids; Audiovisual app; Autism spectrum disorder; Child; Child Development Disorders; Pervasive; Comprehension; Humans; Lipreading; Male; Mobile Applications; Pattern Recognition; Visual; Phonetics; Semantics; Speech Perception; Speech perception; attention; audiovisual aid; child; comprehension; dept.cmd; dept.hls; dept.psy; human; lip reading; male; mobile application; pattern recognition; phonetics; psychology; semantics; speech perception

Ultrasound visual feedback treatment and practice variability for residual speech sound errors - Preston, Jonathan L.; McCabe, Patricia; Rivera-Campos, Ahmed; Whittle, Jessica L.; Landry, Erik; Maas, Edwin (Journal of Speech Language and Hearing Research, 2014)
Purpose: The goals were to (a) test the efficacy of a motor-learning-based treatment that includes ultrasound visual feedback for individuals with residual speech sound errors and (b) explore whether the addition of prosodic cueing facilitates speech sound learning. Method: A multiple-baseline, single-subject design was used, replicated across 8 participants. For each participant, 1 sound context was treated with ultrasound plus prosodic cueing for 7 sessions, and another sound context was treated with ultrasound but without prosodic cueing for 7 sessions. Sessions included ultrasound visual feedback as well as non-ultrasound treatment. Word-level probes assessing untreated words were used to evaluate retention and generalization. Results: For most participants, increases in accuracy of target sound contexts at the word level were observed with the treatment program regardless of whether prosodic cueing was included. Generalization between onset singletons and clusters was observed, as was generalization to sentence-level accuracy. There was evidence of retention during posttreatment probes, including at a 2-month follow-up. Conclusion: A motor-based treatment program that includes ultrasound visual feedback can facilitate learning of speech sounds in individuals with residual speech sound errors.
tex.eissn: 1558-9102 tex.orcid-numbers: McCabe, Patricia/0000-0002-5182-1007 Maas, Edwin/0000-0003-4452-2196 Preston, Jonathan/0000-0001-9971-6321 tex.researcherid-numbers: McCabe, Patricia/E-9435-2010 Maas, Edwin/H-5297-2018 Preston, Jonathan/E-9310-2010 tex.unique-id: ISI:000348195300006
Keywords: Child; Cues; Feedback; Sensory; Female; Humans; Male; Phonetics; Speech; Speech Sound Disorder; Speech Therapy; Ultrasonography; Young Adult; association; child; dept.cmd; diagnostic imaging; echography; female; human; male; pathophysiology; phonetics; physiology; procedures; sensory feedback; speech; speech sound disorder; speech therapy; young adult; ⚠️ Invalid DOI

Neurophysiology of speech differences in childhood apraxia of speech - Preston, Jonathan L; Molfese, Peter J; Gumkowski, Nina; Sorcinelli, Andrea; Harwood, Vanessa; Irwin, Julia; Landi, Nicole (Developmental Neuropsychology, 2014)
Event-related potentials (ERPs) were recorded during a picture naming task of simple and complex words in children with typical speech and with childhood apraxia of speech (CAS). Results reveal reduced amplitude prior to speaking complex (multisyllabic) words relative to simple (monosyllabic) words for the CAS group over the right hemisphere during a time window thought to reflect phonological encoding of word forms. Group differences were also observed prior to production of spoken tokens regardless of word complexity during a time window just prior to speech onset (thought to reflect motor planning/programming). Results suggest differences in pre-speech neurolinguistic processes.
8 citations (Crossref) [2023-10-31] Citation Key Alias: lens.org/138-494-990-805-630 tex.type: [object Object]
Keywords: Adolescent; Apraxias; Child; Evoked Potentials; Female; Humans; Linguistics; Male; Neurophysiology; Speech; adolescent; apraxia; article; child; comparative study; dept.cmd; dept.psy; evoked response; female; human; linguistics; male; neurophysiology; pathophysiology; physiology; speech

Functional brain activation differences in school-age children with speech sound errors: speech and print processing - Preston, Jonathan L.; Felsenfeld, Susan; Frost, Stephen J.; Mencl, W. Einar; Fulbright, Robert K.; Grigorenko, Elena L.; Landi, Nicole; Seki, Ayumi; Pugh, Kenneth R. (Journal of Speech Language and Hearing Research, 2012)
Purpose: To examine neural response to spoken and printed language in children with speech sound errors (SSE). Method: Functional magnetic resonance imaging was used to compare processing of auditorily and visually presented words and pseudowords in 17 children with SSE, ages 8; 6[years; months] through 10; 10, with 17 matched controls. Results: When processing spoken words and pseudowords, the SSE group showed less activation than typically speaking controls in left middle temporal gyrus. They also showed greater activation than controls in several cortical and subcortical regions (e. g., left superior temporal gyrus, globus pallidus, insula, fusiform, and bilateral parietal regions). In response to printed words and pseudowords, children with SSE had greater activation than controls in regions including bilateral fusiform and anterior cingulate. Some differences were found in both speech and print processing that that may be associated with children with SSE failing to show common patterns of task-induced deactivation and/or attentional resource allocation. Conclusion: Compared with controls, children with SSE appear to rely more on several dorsal speech perception regions and less on ventral speech perception regions. When processing print, numerous regions were observed to be activated more for the SSE group than for controls.
23 citations (Crossref) [2023-10-31] Citation Key Alias: lens.org/104-726-704-023-213 tex.orcid-numbers: [object Object] tex.researcherid-numbers: [object Object] tex.unique-id: [object Object]
Keywords: Brain; Cerebral Cortex; Child; Female; Functional magnetic resonance imaging (fMRI); Globus Pallidus; Gyrus Cinguli; Humans; Language Development Disorders; Magnetic Resonance Imaging; Male; Parietal Lobe; Phonetics; Photic Stimulation; Print processing; Reading; Speech; Speech Perception; Speech perception; Speech sound errors; Temporal Lobe; Visual Cortex; article; brain; brain cortex; child; cingulate gyrus; dept.cmd; female; globus pallidus; human; language disability; male; nuclear magnetic resonance imaging; parietal lobe; pathophysiology; phonetics; photostimulation; physiology; reading; speech; speech perception; temporal lobe; visual cortex

Structural brain differences in school-age children with residual speech sound errors. - Preston, Jonathan L; Molfese, Peter J; Mencl, W Einar; Frost, Stephen J; Hoeft, Fumiko; Fulbright, Robert K; Landi, Nicole; Grigorenko, Elena L; Seki, Ayumi; Felsenfeld, Susan; Pugh, Kenneth R (Brain and Language, 2014)
The purpose of the study was to identify structural brain differences in school-age children with residual speech sound errors. Voxel based morphometry was used to compare gray and white matter volumes for 23 children with speech sound errors, ages 8;6-11;11, and 54 typically speaking children matched on age, oral language, and IQ. We hypothesized that regions associated with production and perception of speech sounds would differ between groups. Results indicated greater gray matter volumes for the speech sound error group relative to typically speaking controls in bilateral superior temporal gyrus. There was greater white matter volume in the corpus callosum for the speech sound error group, but less white matter volume in right lateral occipital gyrus. Results may indicate delays in neuronal pruning in critical speech regions or differences in the development of networks for speech perception and production. Copyright © 2013 Elsevier Inc. All rights reserved.
24 citations (Crossref) [2023-10-31] Place: Netherlands Preston, Jonathan L. Haskins Laboratories, 300 George St, Suite 900, New Haven, CT 06511, United States; Department of Communication Disorders, Southern Connecticut State University, New Haven, CT, United States. Electronic address: preston@haskins.yale.edu. Molfese, Peter J. Haskins Laboratories, 300 George St, Suite 900, New Haven, CT 06511, United States. Mencl, W Einar. Haskins Laboratories, 300 George St, Suite 900, New Haven, CT 06511, United States. Frost, Stephen J. Haskins Laboratories, 300 George St, Suite 900, New Haven, CT 06511, United States. Hoeft, Fumiko. Haskins Laboratories, 300 George St, Suite 900, New Haven, CT 06511, United States; Department of Psychiatry, University of California San Francisco, San Francisco, CA, United States. Fulbright, Robert K. Haskins Laboratories, 300 George St, Suite 900, New Haven, CT 06511, United States; Department of Diagnostic Radiology, Yale School of Medicine, New Haven, CT, United States. Landi, Nicole. Haskins Laboratories, 300 George St, Suite 900, New Haven, CT 06511, United States; Yale Child Study Center, New Haven, CT, United States. Grigorenko, Elena L. Yale Child Study Center, New Haven, CT, United States. Seki, Ayumi. Haskins Laboratories, 300 George St, Suite 900, New Haven, CT 06511, United States; Tottori University, Tottori, Japan. Felsenfeld, Susan. Haskins Laboratories, 300 George St, Suite 900, New Haven, CT 06511, United States. Pugh, Kenneth R. Haskins Laboratories, 300 George St, Suite 900, New Haven, CT 06511, United States; Department of Diagnostic Radiology, Yale School of Medicine, New Haven, CT, United States; University of Connecticut, Department of Psychology, Storrs, CT, United States; Department of Linguistics, Yale University, New Haven, CT, United States.
Keywords: *Brain/pa [Pathology]; *Language Development Disorders/pa [Pathology]; *Phonetics; *Speech Perception; Brain; Child; Children; Humans; Language Development Disorders; Magnetic Resonance Imaging; Phonetics; Speech Perception; Speech sound disorders; Speech sound errors; Structural MRI; article; brain region; brain size; child; clinical article; controlled study; corpus callosum; dept.cmd; female; gray matter; human; male; neuroanatomy; occipital gyrus; school child; speech articulation; speech perception; speech sound disorder; speech sound error; superior temporal gyrus; voxel based morphometry; white matter

The relationship between phonological and auditory processing and brain organization in beginning readers - Pugh, Kenneth R.; Landi, Nicole; Preston, Jonathan L.; Mencl, W. Einar; Austin, Alison C.; Sibley, Daragh; Fulbright, Robert K.; Seidenberg, Mark S.; Grigorenko, Elena L.; Constable, R. Todd; Molfese, Peter; Frost, Stephen J. (Brain and Language, 2013)
We employed brain-behavior analyses to explore the relationship between performance on tasks measuring phonological awareness, pseudoword decoding, and rapid auditory processing (all predictors of reading (dis)ability) and brain organization for print and speech in beginning readers. For print-related activation, we observed a shared set of skill-correlated regions, including left hemisphere temporoparietal and occipitotemporal sites, as well as inferior frontal, visual, visual attention, and subcortical components. For speech-related activation, shared variance among reading skill measures was most prominently correlated with activation in left hemisphere inferior frontal gyrus and precuneus. Implications for brain-based models of literacy acquisition are discussed. (C) 2012 Elsevier Inc. All rights reserved.
107 citations (Crossref) [2023-10-31] Citation Key Alias: lens.org/079-059-178-769-726 tex.eissn: [object Object] tex.orcid-numbers: [object Object] tex.researcherid-numbers: [object Object] tex.unique-id: [object Object]
Keywords: Awareness; Brain; Brain Mapping; Child; Child; Preschool; Decoding; FMRI; Female; Humans; Individual differences; Male; Phonological awareness; Photic Stimulation; Psychomotor Performance; Rapid auditory processing; Reading; Speech; Speech Perception; Thalamus; Visual Perception; article; attention; child; dept.cmd; female; frontal lobe; hearing; human; human experiment; inferior frontal gyrus; left hemisphere; male; neurophysiology; normal human; occipital lobe; parietal lobe; phonetics; precuneus; preschool child; printing; reading; school child; speech; task performance; temporal lobe; visual cortex; word recognition

Glutamate and choline levels predict individual differences in reading ability in emergent readers - Pugh, Kenneth R.; Frost, Stephen J.; Rothman, Douglas L.; Hoeft, Fumiko; Tufo, Stephanie N. Del; Mason, Graeme F.; Molfese, Peter J.; Mencl, W. Einar; Grigorenko, Elena L.; Landi, Nicole; Preston, Jonathan L.; Jacobsen, Leslie; et al. (The Journal of Neuroscience, 2014)
Reading disability is a brain-based difficulty in acquiring fluent reading skills that affects significant numbers of children. Although neuroanatomical and neurofunctional networks involved in typical and atypical reading are increasingly well characterized, the underlying neurochemical bases of individual differences in reading development are virtually unknown. The current study is the first to examine neurochemistry in children during the critical period in which the neurocircuits that support skilled reading are still developing. In a longitudinal pediatric sample of emergent readers whose reading indicators range on a continuum from impaired to superior, we examined the relationship between individual differences in reading and reading-related skills and concentrations of neurometabolites measured using magnetic resonance spectroscopy. Both continuous and group analyses revealed that choline and glutamate concentrations were negatively correlated with reading and related linguistic measures in phonology and vocabulary (such that higher concentrations were associated with poorer performance). Correlations with behavioral scores obtained 24 months later reveal stability for the relationship between glutamate and reading performance. Implications for neurodevelopmental models of reading and reading disability are discussed, including possible links of choline and glutamate to white matter anomalies and hyperexcitability. These findings point to new directions for research on gene-brain-behavior pathways in human studies of reading disability. © 2014 the authors.
66 citations (Crossref) [2023-10-31] Citation Key Alias: pop00048 tex.type: [object Object]
Keywords: 4 aminobutyric acid; Aspartic Acid; Brain; Child; Choline; Decoding; Dyslexia; Female; Glutamic Acid; Humans; Individual differences; Individuality; Learning; MRS; Magnetic Resonance Spectroscopy; Male; Phonetics; Phonological processing; Predictive Value of Tests; Reading; Reading disability; Vocabulary; article; behavior; child; choline; decoding; dept.cmd; female; gamma-Aminobutyric Acid; glutamic acid; human; human experiment; individual differences; language ability; linguistics; male; nerve cell differentiation; nerve excitability; normal human; nuclear magnetic resonance spectroscopy; phonetics; phonological processing; priority journal; reading; reading disability; school child; speech